Ageing and the brain. Issue 964 (3rd February 2006) - Peters, R
Abstract : Ageing causes changes to the brain size, vasculature, and cognition. The brain shrinks with increasing age and there are changes at all levels from molecules to morphology. Incidence of stroke, white matter lesions, and dementia also rise with age, as does level of memory impairment and there are changes in levels of neurotransmitters and hormones. Protective factors that reduce cardiovascular risk, namely regular exercise, a healthy diet, and low to moderate alcohol intake, seem to aid the ageing brain as does increased cognitive effort in the form of education or occupational attainment. A healthy life both physically and mentally may be the best defence against the changes of an ageing brain. Additional measures to prevent cardiovascular disease may also be important.